Algorithm for providing assistance for normal and pathological grief - Herasymenko, Larisa; Isakov, Rustam (Psychosomatic Medicine and General Practice, 2025)
The grieving process is a natural human reaction to loss, accompanied by complex psychological, emotional and physiological changes. In most cases, grief is adaptive and ends with the gradual acceptance of the loss. At the same time, in certain situations it can acquire pathological features that require specialized psychotherapeutic intervention. The development of an algorithm for providing assistance with normal and pathological grief contributes to increasing the effectiveness of psychological support and preventing the chronicity of the emotional state. In war conditions, the task of mental health professionals is not only to recognize this condition in time, but also to clearly build an algorithm for helping with grief - from early psychological support for non-pathological grief to targeted therapy for long-term and complicated forms of grief.